EMA-EP regimen, as firstline multiple agent chemotherapy in high-risk GTT patients (stage II–IV). Issue 2 (1st February 2004) - Ghaemmaghami, F.; Modares, M.; Arab, M.; Behtash, N.; Moosavi, A. Z.; Khanafshar, N.; Hanjani, P.
Abstract : Multiple agent chemotherapy in high-risk metastatic gestational trophoblastic tumor patients is a problem for any medical team. In this study, EMA-EP chemotherapy (etoposide, methotrexate, actinomycin, and cisplatinum) was evaluated as firstline chemotherapy to manage high-risk GTT metastatic patients. Seventeen high-risk metastatic patients, including 14 without and 3 with brain metastasis, who were candidates to firstline multiple agent chemotherapy between April 2000 and March 2003 in Vali-e-Asr hospital took part in a prospective study under EMA-EP regimen. EMA-EP was prescribed in two periods: EMA in two consecutive days in week 1 and EP in 1 day in the following week with a week interval between these two (each cycle was repeated every 2 weeks). In brain metastasis group, patients got high-dose medication (methotrexate) together with brain radiotherapy. Remission, toxicity, full dose tolerance, and recurrences of patients were evaluated. Median age of patients was 30 (15–49), and they received 100 courses of chemotherapy including 75 low-dose courses and 25 high-dose courses. 71% of courses were done in full dosage (83% in low dose and 36% in high dose). The most common cause for dosage reduction was leukopenia. Two patients did not complete the regimen, one due to hypersensitivity and the other due to fever and leukopenia leading to death. All others, who received complete courses, achieved remission. In the group without brain metastasis, one case of recurrence was observed. Grade 3 anemia, grade 3 and 4 leukopenia, and grade 3 and 4 thrombocytopenia were observed in 3, 12, and 3% of patients, respectively. In current study, EMA-EP regimen in patients with high-risk metastatic GTN patients (with or without brain metastasis) lead to remission in all patients who completed the treatment courses.